The Normative Relationship Between Moral Values and Justice in Modern Legal Philosophy and Its Consequences for Indonesian Legal Practice - Julio, Christopher Elia; Putra, Gilang; Istimeisyah, Dian; Maniari, Elsa; Triadi, Irwan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study explores the relationship between moral values and justice from the perspective of modern legal philosophy and examines their implementation in Indonesia’s legal practice. The research is grounded in the classical debate between natural law, which positions morality as the source of legal legitimacy, and legal positivism, which separates law from moral considerations. The study aims to analyze how moral values and justice can interact to shape a fair and dignified legal system in Indonesia. Using a normative qualitative approach, the study reviews philosophical theories and national legal practices, including Constitutional Court decisions and the application of restorative justice. The findings reveal that the implementation of moral values and justice in Indonesia’s legal system remains imperfect due to the gap between positive law and substantive justice. Nevertheless, integration efforts continue through progressive legal approaches and human rights, based reforms that emphasize humanity and social justice. In conclusion, moral values and justice are interdependent within modern law, morality provides the ethical foundation for legitimacy, while justice represents its tangible realization in social life.